1985
DOI: 10.1136/adc.60.9.866
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in congenital malformations.

Abstract: Perinatal deaths and major lethal and non-lethal congenital malformations occurring in this hospital from 1979-82 inclusive were related to the ethnic group of the 15 438 mothers. The highest crude perinatal mortality rates occurred in Indian and Pakistani populations (18-3 per 1000 and 24-1 per 1000 respectively). The highest incidence of congenital abnormality also occurred in these groups (13-3 per 1000 and 12*8 per 1000 respectively), but there was considerable variation in the distribution of different ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 3 publications
4
18
1
Order By: Relevance
“…The best evidence of such an effect is, perhaps, from the reduced sterility and increased fertility observed in the population of Southern India (Rao and Inbaraj, 1979). On the other hand, the incidence of genetic disorders within the UK Pakistani population is significantly higher than the incidence in European Caucasians (Terry et al, 1985;Darr and Modell, 1988;Chitty and Winter, 1989;Bundey et al, 1991). Hutchesson et al (1998) determined the frequencies of the ten most common autosomal recessive inborn errors of metabolism within UK Pakistani and UK Caucasian infants.…”
Section: Reproductive Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The best evidence of such an effect is, perhaps, from the reduced sterility and increased fertility observed in the population of Southern India (Rao and Inbaraj, 1979). On the other hand, the incidence of genetic disorders within the UK Pakistani population is significantly higher than the incidence in European Caucasians (Terry et al, 1985;Darr and Modell, 1988;Chitty and Winter, 1989;Bundey et al, 1991). Hutchesson et al (1998) determined the frequencies of the ten most common autosomal recessive inborn errors of metabolism within UK Pakistani and UK Caucasian infants.…”
Section: Reproductive Compensationmentioning
confidence: 99%
“…These findings clearly have health implications, but the estimates cannot be taken at face value on the basis that they do not correspond entirely with the sociological data. Although the consequences of consanguinity to health have been addressed in considerable detail for the UK Pakistani population (Terry et al, 1985;Chitty and Winter, 1989;Bundey et al, 1991), excess homozygosity has not been reported in other UK Asian communities, nor the different possible explanations and their implications for health, although high perinatal mortality has been recorded for UK Indians (Terry et al, 1985;Balarajan and Botting, 1989) and Bangladeshis (Bundey et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognised, but controversial, that consanguinity has an impact on the occurrence of these types of disorders. Congenital abnormalities have been shown to occur more often in the offspring of consanguineous parents than in the offspring of non-related parents (Terry et al 1985;Young and Clarke 1987;WHO 1996a, b;Khoury and Massad 2000). There is also an increased prenatal, perinatal and postnatal mortality in children from ethnic groups that practice consanguinity (Bittles et al 1993;Grant and Bittles 1997), which is largely attributable to an increased incidence of autosomal recessive disorders (Devi et al 1987;Bundey and Aslam 1993;Stoltenberg et al 1999;WHO 2000;Tunçbilek 2001;Mokhtari and Bagga 2003;Bittles 2003;Dawodu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The UK Pakistani population has been studied in detail, in particular because of the clear implications a traditional consanguineous society has for recessive disorders (Terry et al 1985;Darr & Modell, 1988;Chitty & Winter, 1989;Bundey et al 1991). The results of this study suggest that simply identifying broad estimates of the proportion of consanguineous unions, along with an average coefficient of consanguinity, may provide too vague a picture of how disease incidence relates to the risk of congenital disorders.…”
Section: Relevance Of Consanguinity and Substructure To Genetic Healthmentioning
confidence: 99%